2020
DOI: 10.1681/asn.2019020213
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in Chronic Kidney Disease: Updates on Pathophysiology, Diagnosis, and Treatment

Abstract: Anemia is a complication that affects a majority of individuals with advanced CKD. Although relative deficiency of erythropoietin production is the major driver of anemia in CKD, iron deficiency stands out among the mechanisms contributing to the impaired erythropoiesis in the setting of reduced kidney function. Iron deficiency plays a significant role in anemia in CKD. This may be due to a true paucity of iron stores (absolute iron deficiency) or a relative (functional) deficiency which prevents the use of av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
208
0
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(231 citation statements)
references
References 94 publications
(105 reference statements)
1
208
0
22
Order By: Relevance
“…We chose a conservative target for a CKD patient of a Hg of 9 g/dL to not delay surgery more than was necessary, because the surgeons anticipated a low risk of major blood loss. 5 Our patient's age, chronic anemia, and lack of cardiovascular disease suggested this was acceptable. Blood transfusions appear to result in immunomodulation that may lead to an increase in cancer progression.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We chose a conservative target for a CKD patient of a Hg of 9 g/dL to not delay surgery more than was necessary, because the surgeons anticipated a low risk of major blood loss. 5 Our patient's age, chronic anemia, and lack of cardiovascular disease suggested this was acceptable. Blood transfusions appear to result in immunomodulation that may lead to an increase in cancer progression.…”
Section: Discussionmentioning
confidence: 90%
“…Due to elevated levels of hepcidin and blood loss from frequent dialysis and blood draws, more than half of patients with advanced CKD are estimated to have IDA. 5 In practice, there may be concerns surrounding the robustness in Hg increase within the short time period between the preoperative visit and surgery especially in patients with CKD and cancer due to erythropoietin deficiency and bone marrow suppression. We discuss a case where a patient with stage 4 CKD, severe anemia, endometrial cancer, and vaginal bleeding benefitted from preoperative IV iron and erythropoietin treatment.…”
mentioning
confidence: 99%
“…Functional ID is characterized by restricted iron availability, commonly due to inflammatory conditions. Inflammation induces the release of hepcidin and therefore, reduces gastrointestinal iron absorption as well as higher mobilization of stores in the reticuloendothelial system (8).…”
Section: Anemia In Nd-ckd: Common and Harmfulmentioning
confidence: 99%
“…13,39,40 In addition, AID can result from malnutrition, vegetarian diets (which cause AID but a priori with no anemia), or vegan diets (which are believed to cause AID with anemia). 28,41,42 Blood donors are also exposed to AID, as are patients with kidney failure, 18,43 which is particularly common in OAs. It has been shown that moderate chronic renal failure is present in almost all patients aged 80 and older hospitalized in a geriatric unit.…”
Section: Causes Of Aidmentioning
confidence: 99%
“…44 In kidney failure, AID, due to excessive blood loss and an abnormality of iron reabsorption, worsens anemia secondary to a defect in the synthesis of erythropoietin. 43 Finally, chronic alcohol abuse may be complicated by AID. 28 It is imperative to keep in mind that OAs often develop AID for multiple and interrelated reasons.…”
Section: Causes Of Aidmentioning
confidence: 99%